2010
DOI: 10.2298/sos1003345j
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CaCO3 addition on the crystallization behavior of ZnO crystal glaze fired at different gloss firing and crystallization temperatures

Abstract: A glazed ceramic product with crystalline structure gives an artistic effect. In this study, the effects of calcium carbonate (CaCO3) addition into glaze batches on the crystallization behavior of crystal glaze were studied. Samples were fired at different gloss firing temperatures ranging from 1000-1200°C with 1060°C crystallization temperature. Xray diffraction (XRD) and energy dispersive X-ray spectrometer (EDX) analysis of the phases identified these crystals as willemite (Zn2SiO4) in the form of sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…When the amount of TiO 2 is increased, predominantly titanate and secondly zinc orthotitanate crystals are formed after heat treatment. It is reported that willemite is the main phase of zinc containing crystalline glazes [6,17]. In this study, a well-developed macro-crystal glaze surface was achieved in the ZnO based Z3 glaze with willemite crystallization.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…When the amount of TiO 2 is increased, predominantly titanate and secondly zinc orthotitanate crystals are formed after heat treatment. It is reported that willemite is the main phase of zinc containing crystalline glazes [6,17]. In this study, a well-developed macro-crystal glaze surface was achieved in the ZnO based Z3 glaze with willemite crystallization.…”
Section: Resultsmentioning
confidence: 74%
“…Its unmatured surface is related to the high levels of Al 2 O 3 and SiO 2 . Depending on the type of compositions and clay bodies, the gloss firing temperatures of crystalline glazes can vary from 1250 to 1300 1C [6,7,11,12,[17][18][19][20]. In contrast with previous studies, R 2 O-RO-(ZnO)-Al 2 O 3 -(TiO 2 )-SiO 2 system raw macro-crystal glazes were successfully developed at a relatively low maximum firing temperature of 1205 1C, promising a time consuming and cost effective production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the literature review not reported any information about hardystonite in glazes. Jamaludin [11] studied influence of CaCO 3 addition on the phase crystallization in willemite glass-crystalline glazes. Author focused on final crystalline phase composition of glaze, and probably, this was a reason of not registered a hardystonite in glaze.…”
Section: Introductionmentioning
confidence: 99%